2016
DOI: 10.1016/j.cortex.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The functional subdivision of the visual brain: Is there a real illusion effect on action? A multi-lab replication study

Abstract: It has often been suggested that visual illusions affect perception but not actions such as grasping, as predicted by the "two-visual-systems" hypothesis of Milner and Goodale (1995, The Visual Brain in Action, Oxford University press). However, at least for the Ebbinghaus illusion, relevant studies seem to reveal a consistent illusion effect on grasping (Franz & Gegenfurtner, 2008. Grasping visual illusions: consistent data and no dissociation. Cognitive Neuropsychology). Two interpretations are possible: eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(96 citation statements)
references
References 67 publications
(208 reference statements)
7
88
1
Order By: Relevance
“…However, the small correlation reported in our study was mainly explained by the big context condition. Although we found a small correlation with a relatively small sample size, the correlation that we found between perception and action is in accordance with similar (low) correlations in grasping 51 . Taken together, our results partially confirm that the MT is scaled according to the perceived target size; the scaling was present (only) when the target looked smaller.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the small correlation reported in our study was mainly explained by the big context condition. Although we found a small correlation with a relatively small sample size, the correlation that we found between perception and action is in accordance with similar (low) correlations in grasping 51 . Taken together, our results partially confirm that the MT is scaled according to the perceived target size; the scaling was present (only) when the target looked smaller.…”
Section: Discussionsupporting
confidence: 89%
“…Note that our believe that obstruction avoidance has played a negligible role, if any, in our present study is supported by a large, multi-lab study of Kopiske et al . 51 that examined the obstruction avoidance hypothesis in 144 participants. They found no evidence that the effects of visual illusions on grasping could be explained by obstruction avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, numerous studies report size-contrast effects on perception but not action (e.g., Aglioti et al, 1995; Haffenden and Goodale, 1998; Marotta et al, 1998; Haffenden et al, 2001). On the other hand, there are numerous other studies that do not provide evidence for such dissociation with similar size-contrast effects across perception and action tasks (e.g., Pavani et al, 1999; Van Donkelaar, 1999; Franz et al, 2000; Glover and Dixon, 2001; Kopiske et al, 2016). Along these lines, Corbett and Song (2014) demonstrated that visually guided actions directed to test circles presented in regions adapted to large/small mean sized displays were initially biased in-line with a persistent perceptual aftereffect.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, behavioral studies of healthy subjects using geometrical illusions also support the proposal for functionally distinct visual systems for perceptual judgments and action (van Doorn et al, 2007; Bruno et al, 2008; Ganel et al, 2008; Stöttinger et al, 2010, but see for a recent debate Kopiske et al, 2016 and Whitwell and Goodale, 2016). The observation that illusions, most notably the Müller-Lyer illusion, can deceive perceptual judgments while visually controlled movements (often pointing) toward the same object are less affected, is interpreted as evidence for a distinction between the two visual systems.…”
Section: Introductionmentioning
confidence: 66%